Patient‐Reported Symptoms and Mental Health Event Risks in Adolescents and Young Adults With Cancer - Sumit Gupta; Qing Li; Paul Nathan; Paul Kurdyak; Nancy Baxter; Rinku Sutradhar; Natalie Coburn (Cancer Medicine)
ABSTRACT Introduction Adolescents and young adults (AYA) with cancer are at risk of adverse mental health outcomes during and after treatment. Tools identifying AYA at the highest risk would guide screening and interventions. We determined whether self‐reported symptoms following cancer diagnosis were associated with early and late severe mental health events (SMHEs). Methods Ontario AYA diagnosed with cancer aged 15–29 between 2010 and 2018 were identified and linked to healthcare databases, including one capturing self‐reported Edmonton Symptom Assessment System (ESAS) scores at cancer‐related visits. Scores for depression, anxiety, and poor well‐being were categorized as not measured, mild, moderate, or severe. SMHEs were defined as mental health‐related Emergency Department visits or hospitalizations. We determined the association of ESAS scores with subsequent early SMHEs (< 5 years). Among 5‐year survivors, we determined the association between the maximum ESAS score within 1 year of cancer diagnosis and late SMHEs (occurring > 5 years from cancer diagnosis). Results Among 5435 AYA, symptom severity was associated with subsequent SMHE risk. AYA who reported severe versus mild anxiety were at > 3‐fold higher risk of subsequent early SMHEs [adjusted hazard ratio (aHR) 3.6, 95th confidence interval (CI) 1.9–6.7; p < 0.001]. Among 3518 (64.7%) 5‐year survivors, symptom severity predicted late SMHE. At 5 years postcancer diagnosis, those who reported severe versus mild depression within 1 year following cancer diagnosis were at 3‐fold elevated risk (aHR 3.0, 95 CI 1.8–4.9; p < 0.0001). Conclusion Systematic symptom screening early postcancer diagnosis identifies AYA at high risk of both early and late SMHEs who may benefit from targeted screening and interventions.